Wajah Kota Apa yang Kita Inginkan? Dapatkah Kita Membuatnya? - Patta, Jhonny; Kombaitan, Benedictus (Center for Research and Community Services ITB, 2003)
Since its early history , city planning has dealt with different models of city. At the turn of the twentieth century, it was a discipline of design that focused on how to design the ideal-city. By the mid 1930s, city planning became a discipline of social science that focused on how to pursue the rational comprehensive city. By the early 1960s, on one side, city planning became a discipline of urban process and outcome. By the early 1980s, city planning became a discipline of management science that focused on how to use public money efficiently and effectively for the desired future city. By the early 1990s, city planning became a discipline of information technology that focused on how to provide information for social interaction and social future. By the early 2000s, city planning became a discipline of scientific design that focused on how to design the new urbanism. This paper deals with these different models, and analyzes whether city planners can make the model of the city they want.